DERIVATION OF RELATIVE CLAUSES AS COMPLEX SYNTACTIC CONSTRUCTIONS - Xamrayeva Zebiniso Xaydar qizi (Innovate Conferences, 2026)
The derivation of relative clauses constitutes a fundamental aspect of complex syntactic constructions, as relative clauses enable speakers to encode additional descriptive, restrictive, and explanatory information within a single nominal unit. This literature review examines major theoretical approaches to the derivation of relative clauses with particular reference to English and Uzbek. Drawing on generative, functional, cognitive, and typological frameworks, the study synthesizes existing research on syntactic embedding, movement, morphological marking, and the syntax–semantics interface. The review highlights how English primarily relies on relative pronouns and complementizers in the derivation of relative clauses, whereas Uzbek employs participial and non-finite verb forms as key derivational mechanisms. By comparing these two typologically distinct languages, the article demonstrates both universal principles of clause embedding and language-specific strategies of syntactic derivation. The analysis also considers semantic, pragmatic, and cognitive factors influencing relative clause formation and interpretation. The review concludes that the derivation of relative clauses is a multifaceted process shaped by the interaction of syntactic structure, semantic relations, and morphosyntactic resources, and it underscores the importance of cross-linguistic perspectives for a comprehensive understanding of complex syntactic constructions.
Keywords: Relative clauses, complex syntactic constructions, syntactic derivation, clause embedding, syntax–semantics interface, participial constructions, relative pronouns, English and Uzbek comparison, cross-linguistic syntax, complex sentences.